Pengaruh Model Pembelajaran Kooperatif Two Stay Two Stray Berbantuan Mind Maping Terhadap Kemampuan Pemecahan Masalah Siswa Pada Pembelajaran Sosiologi Kelas X ( Sepuluh ) Ma Nurul Fata Tahun Pelajaran 2021/2022 - Sova Lailaturrahma; Miftahus Surur; Zainul Munawwir (Departement of Mathematics Education, 2023)
Problem solving ability is the process taken by a person to solve the problems he faces until the problem is no longer a problem for him. Sociology learning as an abstract learning is not enough to be delivered with theory and find answers, but it is necessary to have learning media and learning models that varied,. The media used is mind mapping. In addition to media, learning models are also needed in the learning process. The model used in learning is a two-stay two-stray cooperative learning model. The purpose of this is to determine the effect of the learning model used on students' problem solving abilities. The method used in this study is a quantitative method, with the results showing that the use of the two stay two stray cooperative learning model can improve students' problem solving abilities.